Thermodynamic analysis of a hybrid energy storage system based on compressed air and liquid air. (September 2015) - Kantharaj, Bharath; Garvey, Seamus; Pimm, Andrew
Abstract: As renewable electricity generation capacity increases, energy storage will be required at larger scales. Compressed air energy storage at large scales, with effective management of heat, is recognised to have potential to provide affordable grid-scale energy storage. Where suitable geologies are unavailable, compressed air could be stored in pressurised steel tanks above ground, but this would incur significant storage costs. Liquid air energy storage, on the other hand, does not need a pressurised storage vessel, can be located almost anywhere, and has a relatively large volumetric exergy density at ambient pressure. However, it has lower roundtrip efficiency than compressed air energy storage technologies. This paper analyses a hybrid energy store consisting of a compressed air store at ambient temperature, and a liquid air store at ambient pressure. Thermodynamic analyses are then carried out for the conversions from compressed air to liquid air (forward process) and from liquid air to compressed air (reverse process), with notional heat pump and heat engine systems, respectively. Preliminary results indicate that provided the heat pump/heat engine systems are highly efficient, a roundtrip efficiency of 53% can be obtained. Immediate future work will involve the detailed analysis of heat pump and heat engine systems, and the economics of the hybrid energy store.